An evaluation of the physical plant of the University Elementary School, University of the Philippines System - Javier, Remedios Garcia 1922-
Although the school is accessible to the present school population, the site has a limited area and has no adequate parking area. Classrooms are pleasant and attractive but space is too limited for effective teaching; there are no special rooms such as auditorium and gymnasium and there is limited reading space in the library. The physical plant is far from adequate to meet the stated goals of the College, namely: excellence in instruction, research, community service, development-oriented leadership, and providing for the requirements of ongoing programs.
Thesis (M.Ed.)--University of the Philippines.
Keywords: University of the Philippines -- Elementary School